PENGARUH TANGIBILITY, PROFITABILITAS, GROWTH, RISIKO BISNIS DAN LIKUIDITAS TERHADAP KEBIJAKAN HUTANG (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Abubakar, Dwi Yuniarti; Daat, Sylvia Christina; Sanggenafa, Mariolin A. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The research aims to analyze the influence oftangibility, profitability, growth, business risk, and liquidity to debt policy. This research is repurposed to review the influence oftangibility, profitability, growth, business risk, and liquidity of debt policy. Financial report is obtained by access to www.idx.co.id. The number of samples obtained in this study was as much as 178 samples. The analytical techniques used in this study are multiple linear regression to obtain a thorough picture of the relationship between the variables of one another. The results in this study show that profitability, business risk, liquidity, and size of the company have an influence and significance to the debt policy. While tangibility, growth, and age companies do not affect the debt policy.